The Influence of Servant Leadership, Work Motivation, and Work Commitment on Public Elementary School Teachers’ Performance - Tampi, Yuni; Suriansyah, Ahmad; Noorhapizah, Noorhapizah (Journal of Elementary Educational Research, 2025)
This study aims to analyze the influence of school principals' servant leadership, work motivation, and job commitment on the performance of public elementary school teachers in Dusun Timur District. A quantitative correlational approach was used, with path analysis as the main analytical technique. The sample consisted of 169 teachers selected proportionally from a population of 292. Data were collected through a structured Likert-scale questionnaire. The findings revealed that: (1) servant leadership, work motivation, and job commitment each had a significant direct effect on teacher performance; (2) servant leadership and work motivation significantly influenced job commitment; and (3) job commitment served as a significant mediating variable in the relationship between servant leadership and work motivation on teacher performance. The coefficient of determination showed that the three independent variables explained 56% of the variance in teacher performance, with the remaining 44% influenced by other factors. These results emphasize that a servant leadership style and strong intrinsic motivation can significantly enhance teachers’ job commitment and performance. Therefore, strengthening principals' leadership capacities and enhancing teachers' internal motivation are effective strategies for improving the quality of basic education.